2013
DOI: 10.1088/1674-4527/13/5/009
|View full text |Cite
|
Sign up to set email alerts
|

Grids of rotating stellar models with masses between 1.0 and 3.0M

Abstract: We calculated a grid of evolutionary tracks of rotating models with masses between 1.0 and 3.0 M ⊙ and a resolution δM ≤ 0.02 M ⊙ , which can be used to study the effects of rotation on stellar evolutions and on the characteristics of star clusters. The value of ∼2.05 M ⊙ is a critical mass for the effects of rotation on stellar structure and evolution. For stars with M > 2.05 M ⊙ , rotation leads to an increase in the convective core and prolongs the lifetime of main sequence (MS); rotating models evolve slow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 39 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…This reflects that rotation and convection overshoot may be important in the evolution of the Sun. Moreover, rotation plays an important role in the formation of the extended main-sequence turnoff of intermediate-age massive star clusters (Yang et al 2013a(Yang et al , 2013b,and convection overshoot plays an essential role in explaining some of thecharacteristics of solar-like oscillations Figure 6. Distributions of the ratios of small to large separations, r 02 and r 13 , as a function of frequency.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…This reflects that rotation and convection overshoot may be important in the evolution of the Sun. Moreover, rotation plays an important role in the formation of the extended main-sequence turnoff of intermediate-age massive star clusters (Yang et al 2013a(Yang et al , 2013b,and convection overshoot plays an essential role in explaining some of thecharacteristics of solar-like oscillations Figure 6. Distributions of the ratios of small to large separations, r 02 and r 13 , as a function of frequency.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Rotational and turbulent mixing can reduce the surface helium settling (Proffitt & Michaud 1991;Yang & Bi 2006;Turck-Chièze et al 2010;Yang et al 2013aYang et al , 2013b,but the position of the CZ base of rotating models with low Z is too shallow (Yang & Bi 2007). Montalbán et al (2006) and Castro et al (2007) showed that convective overshoot can bring the depth of the CZ into agreement with the seismic value.…”
Section: Rotating Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) The Von Zeipel effect and the mixing of elements can affect the instability of convection by changing the radiative and adiabatic temperature gradients. If the convective core increases, the lifetime of the MS will be prolonged, and vice versa (Maeder 1987;Talon et al 1997;Maeder & Meynet 2000;Yang et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Bastian & de Mink (2009) only calculated the evolution of a star with the mass of 1.5 M ⊙ , assuming that the results for the star can be applied to others. In fact, the effects of rotation on the structure and evolution of stars depend on the mass of stars for a given rotation rate (Maeder & Meynet 2000;Yang et al 2013a). On the contrary, however, in the models of Girardi et al (2011), the effects of the mixing may be more efficient, which results in the fact that their rotating models have a higher effective temperature than non-rotating ones in the late stage of the MS for stars of any mass.…”
Section: Introductionmentioning
confidence: 99%